Outsiders-within: The professional development history of African-American tenured female faculty in the white research academy - Mary Vianna Alfred (Adult Education Research Conference, 1996)
African American female faculty continue to be underrepresented in White research universities. Those who make entry are often at the bottom of the hierarchy and are among the ones least likely to be tenured. Despite major obstacles, a few Black women are receiving tenure in the White research academy. This study examines the professional development history of five of these tenured women to gain insight into the experiences that have contributed to their successful career in the White research academy.